Innovative Approaches in Acyl Sonogashira Coupling: Impact of Supported CuNPs and Cu-PdNPs Nanocatalysts - Santiago Stabile; Gabriel Radivoy (Chemistry Proceedings)
In this work, we present our findings on the acyl Sonogashira coupling catalyzed by copper nanoparticles (CuNPs) or bimetallic copper–palladium (4:1 molar ratio) nanoparticles (Cu-PdNPs) immobilized in various inorganic materials. Both catalysts allowed the synthesis of ynones in good to excellent yields. Cu-PdNPs supported on Celite exhibit high activity, allowing reactions to proceed at room temperature, whereas the monometallic CuNPs catalysts required reactions to be carried out at 80 °C. In addition, Cu-PdNPs/Celite can be also used in Sonogashira coupling reactions with iodoarenes. Both types of catalysts can be reused without any pre-treatment after separation from the reaction medium and subsequent washing.